Tuning the selectivity of CO2 hydrogenation using ceramic hollow fiber catalytic modules - Jogdand, Shunottara M.; Bedadur, Prachiti R.; Torris, Arun; Kharul, Ulhas K.; Naidu, V. Satyam; Devi, R. Nandini (Reaction Chemistry & Engineering, 2021)
The unique structural features and advantageous pore distributions of alumina hollow fibers can be exploited to tune the selectivity in heterogeneous catalysis. Formation of a finger-like cavity structure is the unique characteristic of the phase inversion method, which provides a larger surface area to volume ratio desirable for catalytic reactions. This feature, along with a highly porous sandwiched skin layer, makes this architecture superior to conventional powder catalysts or other structured catalyst forms like monoliths. Alumina hollow fibers are prepared by the modified phase inversion method and characterized for their pore size and distribution. Ni metal nanoparticles are uniformly deposited in the Al2O3 hollow fibers to prepare a Ni/Al2O3 catalyst and tested for the CO2 methanation reaction. Suitable reactor and catalyst loading methods are designed and optimized to achieve higher CO2 to methane conversion in a temperature range of 225 to 400 degrees C. The alpha-alumina phase, which is usually reported to be a poor support for Ni in CO2 methanation in the conventional fixed bed configuration, showed high activity when modulated as hollow fibers. Also, the selectivity to CH4 is enhanced and minimal CO formation is observed. The kinetic rate expressions are simulated for the prediction of methane and CO gas evolution at the outlet with temperature. The experimental results for the gas composition are in good agreement with the model predictions. The advantage of such a module reactor is explained based on the mass transfer limitations and consequently the reaction time constants arrived at from the predicted gas compositions.

Addressing challenges in sealing of scalable multifiber module for O-2 enrichment using LSCF membranes - Jogdand, Shunottara M.; Bedadur, Prachiti R.; Torris, Arun; Agrawal, Ravi; Kharul, Ulhas K.; Devi, R. Nandini (International Journal of Applied Ceramic Technology, 2022)
Scalable and multifiber modules in oxygen separation face huge challenges due to difficulty in integrating all the necessary components, especially in sealing the fibers in a gas tight module. Here, we report our findings on design and fabrication of a multifiber La0.6Sr0.4Co0.2Fe0.8O3-delta (LSCF)-based module, which can be scaled up. The focus is on sealing ceramic-metal interfaces by layering of sealants of varying thermal properties. We have also incorporated the use of dead ended fibers to minimize ceramic-metal interfaces in the hot zones and present a new method for dead ending by flame melting. Pressurizing the air inlet feed from either bore side or shell side is detrimental to the structural integrity of the fibers. A thorough characterization of the fresh and spent fibers is also carried out using X-ray tomography and electron microscopy, which indicates effect of temperature and pressure on the fibers.
Keywords: Characterization; permeability; Perovskites

Continuous flow hydrodeoxygenation of lignin-derived guaiacol to cyclohexanol over durable Al2O3 hollow fiber supported co catalyst - Singh, Dheerendra; Jogdand, Shunottara M.; Devi, R. Nandini; Dhepe, Paresh L. (ChemCatChem, 2025)
The drive to decarbonize the chemical, oil, and gas industries through use of bio-derived resources is intensifying. This study focuses on converting lignin-derived phenolic compounds into cyclohexanol, a precursor for adipic acid production. The alumina hollow fiber supported cobalt catalyst (5Co/AHF@capillary) prepared by capillary action method was found to consist cobalt in both metallic and +delta oxidation states. Initial tests in a batch-mode reactor showed promising results, with 5Co/AHF@capillary catalyst demonstrating catalytic activity comparable to Ru/Al2O3 systems (225 degrees C, 1 MPa H-2, 4 h), achieving similar to 86% cyclohexanol yield in guaiacol hydrodeoxygenation reactions. The catalytic system was then adapted for continuous flow reactors under milder conditions (300 degrees C, 2.5 MPa H-2, 18 mL min(-1)), resulting in 83% guaiacol conversion and 74% cyclohexanol yield. The durability of the catalyst was checked for >80 h and results claim that catalyst was active in yielding consistent results. The roles of catalyst preparation method, hydrogen pressure, solvent, WHSV were thoroughly checked and discussed.
Keywords: biomass valorization; Carbon; Co/Al2O3; Cyclohexanol; lignin

Understanding the structural characteristics of modified ceramic hollow fiber oxygen transport membranes through in silico tomography simulation study - Jogdand, Shunottara M.; Sharma, Jyoti; Khilari, Rushikesh S.; Mahajan, Digvijay P.; Patil, Prashant; Pol, Harshavardhan V.; Torris, Arun; Agrawal, Ravi; Kharul, Ulhas K.; Devi, R. Nandini (ACS Applied Materials & Interfaces, 2025)
Design and development of integrated membrane reactor systems are gaining attention as a sustainable solution capable of performing multiple functions in a single reactor. Membrane reactors made of mixed ionic-electronic conduction materials dosing pure O to the reactions can be exploited for various catalytic processes. In this case, micro- and macrostructures of the membrane surface play a significant role in the permeation performance of membranes, and understanding these parameters prior to scaling up to modules is imperative. Here, 3D X-ray tomography imaging, a versatile nondestructive instrumental technique, is used in understanding the structural behavior of the membrane walls at different structural alignments, leading to anticipation of fouling areas upon assembling membrane reactors. La0.6Sr0.4Co0.2Fe0.8O3-delta hollow fiber membranes are fabricated by the phase inversion method and further modified by the optimized acid etching technique. In silico simulations on different morphologies before and after surface modifications are carried out under varying flow rates at nonambient temperatures to mimic real experimental conditions. Critical parameters such as gas velocity, pressure exerted on cavity walls, and strain, dictating structural integrity of the fibers under experimental conditions, were evaluated. As a result of the assessment, the surface-modified structural morphology with finger-like cavities initiating from the inner wall of the membrane was found to be robust. Increase in the pore size, nonuniform pore size distribution, and irregular and interdigitated cavities formed in outer fingered membranes after multiple surface treatments led to an similar to 5 fold increase in the average pressure exerted at the cavity walls when compared to inner fingered membranes. Strain profile generated for inner fingered membranes shows homogeneous distribution of strain for the applied stress throughout the 3D geometry of the membrane. This detailed structural analysis of the membrane will help in building a more robust and efficient system for scale-up applications.
Keywords: 3D X-ray tomography; in silico simulation; oxygen transport membranes; perovskite; phase inversionmethod